2020
DOI: 10.1002/tox.23072
|View full text |Cite
|
Sign up to set email alerts
|

Carboxy terminus of HSP70‐interacting protein (CHIP) attenuates the stemness of thyroid cancer cells through decreasing OCT4 protein stability

Abstract: Cancer cell stemness results in the occurrence and progression of tumors and Oct4 (octamer‐binding transcription factor) has been confirmed to be a critical contributor and marker of cancer cell stemness. Here, we aimed to explore the underlying mechanisms contributing to Oct4 protein stability, which is necessary for thyroid cancer (TC) cell stemness. We indicated that carboxy terminus of HSP70‐interacting protein (CHIP) protein was lowly expressed in TC tissues and cells, and positively correlated with the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated that the E3 ubiquitin ligase STUB1 exhibits a tumor suppressor effect by promoting ubiquitination and degradation of multiple oncogenes in various cancers, including lung cancer [16,17] , breast cancer [7] , prostate cancer [8][9][10] , gastric cancer [21] , colorectal cancer [14] , and thyroid cancer [32] . For example, STUB1 functions as a tumor suppressor in ovarian carcinoma by promoting ubiquitination and degradation of PKM2 [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the E3 ubiquitin ligase STUB1 exhibits a tumor suppressor effect by promoting ubiquitination and degradation of multiple oncogenes in various cancers, including lung cancer [16,17] , breast cancer [7] , prostate cancer [8][9][10] , gastric cancer [21] , colorectal cancer [14] , and thyroid cancer [32] . For example, STUB1 functions as a tumor suppressor in ovarian carcinoma by promoting ubiquitination and degradation of PKM2 [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, CHIP is reported to repress tumor metastasis in lung cancer by polyubiquitination of ovarian tumor domain-containing protein 3 to promote its degradation [ 28 ]. Interestingly, it was revealed that CHIP could alleviate the stemness of thyroid cancer cells through downregulation of Oct4 protein stability [ 29 ]. Additionally, CHIP mediates CD166 protein stability via the ubiquitin proteasome system, thereby repressing the properties of CSCs in head and neck cancer [ 21 ].…”
Section: Discussionmentioning
confidence: 99%